Evaluations hematological and biochemical by the use of sodium diclofenac, meloxicam and firocoxib in rats - Barbosa, Cristiane Moraes [UNESP]; Sakate, Michiko [UNESP]; Camplesi, Annelise Carla [UNESP]; Vailati, Maria do Carmo Fernandez [UNESP]; Moraes, Lívia Fagundes [UNESP]; Takahira, Regina Kiomi [UNESP] (My University, 2010)
This work has evaluated the hematological and biochemical profile by the use of sodium diclofenac, meloxicam and firocoxib in Wistar rats. The rats were distributed in groups: G1 (control), G2 (diclofenac sodium: 15 mg/kg), G3 (meloxicam: 2.0 mg/ kg), G4 (meloxicam: 10.0 mg/ kg), G5 (firocoxib: 5.0 mg/ kg) e G6 (firocoxib: 25.0 mg/ kg). The drugs were administered intragastrically (gavage) once a day, during five days and evaluated in three moments: M1 (48 hours after the beginning of the treatment), M2 (96 hours after the beginning of the treatment) and M3 (72 hours after the ending of the treatment). In each moment of each group, five to seven animals were evaluated and laboratory exams were performed. There were no significant changes observed in the biochemical and hematological parameters by the use of meloxicam and firocoxib. One of the effects of the sodium diclofenac was eritrogram variation as hematocrit, erythrocytes, hemoglobin decrease during the treatment. In addition, the platelets and total white blood cells counts did not change except for basophil. There was no changes in AST, ALP, GGT, urea, creatinine, sodium, potassium values. However, the values of protein, globulin and albumin decreased. It was concluded that diclofenac sodium does not provide large variations in the hemogram and biochemical profile than the meloxicam and firocoxib do not provide delletery effects in laboratories tests.
Avaliações hematológicas e bioquímicas do uso de diclofenaco de sódio, meloxicam e firocoxibe em ratos
Keywords: Firocoxib; Laboratories parameters; Meloxicam; Rats; Sodium diclofenac; Animalia; Rattus; Rattus norvegicus